Caught in the crossfire : children of gay and lesbian parents - Williams, Sandra R.; Lighston, Heather J.; Films for the Human & Sciences (Firm) (Princeton, NJ : Films Media Group, 2004)
Seven ethnically diverse children (ages 8 to 16) from four families express their feelings about living with gay and lesbian parents
Cinematographer, Sara Rashad ; editors, Michele Erausquin,Matt Hill ; music, Steve Pradd
DVD format
Keywords: Children of gay parents -- United States; Lesbians -- United States; Gay fathers -- United states -- Family relationships; Lesbian mothers -- United States -- Family relationships; Bisexual parents -- United States -- Family relationships